Too good to be true? The Creation of the People of Israel - Lemche, Niels Peter (Die Welt des Orients, 2020)
In the Bible we find an emphasis of the ethnic origins of ancient Israel. It is really as if it was the self-understanding of a highly sectarian group excluding everybody except those totally investing their intellect in the worship of one deity, the God of Israel. Over the last generation the study of the story of ancient Israel as found in the Old Testament has in an increasing degree removed its foundation in real history - things that happened - and turned it into a narrative with only casual relations to the past of the land of Israel - or Palestine. Accordingly, the subjects of study are today how and why this narrative came into being and about authorship.